2002
DOI: 10.3763/ehaz.2002.0406
|View full text |Cite
|
Sign up to set email alerts
|

Disaster vulnerability of businesses in the 2001 Nisqually earthquake

Abstract: This paper examines the impacts of the February, 2001, Nisqually earthquake on businesses. Focusing on two hard-hit business districts in Seattle, the study investigates the extent of losses, patterns of disparities, and underlying loss factors. A conceptual framework is proposed of how business vulnerability dimensions contribute to disaster loss. Interviews were conducted with owners and managers of 107 businesses. Data were gathered on impacts, methods of finance, and disaster preparedness. Results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 12 publications
3
33
1
Order By: Relevance
“…Webb et al (2002) found that retail and wholesale businesses in Florida were less likely to recover from Hurricane Andrew than other types of organizations. Chang and Falit-Baiamonte (2003) similarly found that a far greater percentage of retail businesses suffered major economic loss following the 2001 Nisqually earthquake in Seattle than did business in other sectors. And Boarnet (1998) also concluded that the highest percentage of businesses experiencing loss after the Northridge earthquake was in the retail sector.…”
Section: Business Characteristicsmentioning
confidence: 86%
See 2 more Smart Citations
“…Webb et al (2002) found that retail and wholesale businesses in Florida were less likely to recover from Hurricane Andrew than other types of organizations. Chang and Falit-Baiamonte (2003) similarly found that a far greater percentage of retail businesses suffered major economic loss following the 2001 Nisqually earthquake in Seattle than did business in other sectors. And Boarnet (1998) also concluded that the highest percentage of businesses experiencing loss after the Northridge earthquake was in the retail sector.…”
Section: Business Characteristicsmentioning
confidence: 86%
“…However, several studies of disaster impacts on businesses have failed to find any significant association between disaster preparation and business recovery (e.g., Chang & Falit-Baiamonte, 2003;Dahlhamer & Reshaur, 1996;Webb et al, 2002). The mere existence of a disaster plan does not guarantee that organizational members executed the plan successfully including all of its details at the appropriate time before a disaster.…”
Section: Pre-disaster Preparationmentioning
confidence: 95%
See 1 more Smart Citation
“…Social vulnerability theory posed a substantially different argument. This theory argues that societal conditions (such as socioeconomic status, race or ethnicity and location) are as important as physical circumstances in assessing the impact of a disaster (Chang & Falit-Baiamonte, 2002). In this instance, the primary sampling unit is the individual, business or community.…”
Section: Theoretical Approachesmentioning
confidence: 98%
“…A growing body of empirical research has helped inform these changing concepts of recovery. Some studies have focused on households and housing (Bates, 1982;Bolin, 1982Bolin, , 1993Stanford, 1991, 1998;Comerio, 1998;Hirayama, 2000;Rubin and Popkin, 1990) or on business recovery (Alesch et al, 2001;Chang and FalitBaiamonte, 2002;Kroll et al, 1991;Webb et al, 2000), often gathering data through onetime surveys. Bates and Peacock (1993) develop a measure of disaster impact and recovery for crossnational comparison, but this domestic assets approach relies on indepth primary data collection and focuses on the household level.…”
Section: Prior Studies On Urban Disaster Recoverymentioning
confidence: 99%